179k views
2 votes
-9+n=-18 step by step solution

User KumarA
by
5.3k points

1 Answer

5 votes
Step 1: -9+n=-18. You would add the inverse to both sides, meaning you’d add nine to the negative nine to cancel it out and then then 9 to -18.

-9+n=-18
+9 +9

That would leave you with the equation: n=-9, since -18 plus a positive 9 equals a negative nine. You’re final answer is n= -9.

You can check you answer by substituting the variable with the solution (-9).
-9 + -9= -18
User Jared Egan
by
5.3k points